Opening the “Black Box”: Functions of the Frontal Lobes and Their Implications for Sociology - Firat, Rengin B. (Frontiers in Sociology, 2019)
Previous research has provided theoretical frameworks for building inter-disciplinary bridges between sociology and the neurosciences; yet, more anatomically or functionally focused perspectives offering detailed information to sociologists is largely missing from the literature. This manuscript addresses this gap by offering a comprehensive review of the functions of the frontal lobes, arguably the most important brain region involved in various ‘human’ skills ranging from abstract thinking to language. The paper proposes that the functions of the frontal lobe sub-regions can be divided into three inter-related hierarchical systems with varying degrees of causal proximity in regulating human behavior and social connectedness: (a) the most proximate, voluntary, controlled behavior—including motor functions underlying action-perception and mirror neurons, (b) more abstract motivation and emotional regulation—such as Theory of Mind and empathy, and (c) the higher-order executive functioning—inhibition of racial bias. The paper offers insights from the social neuroscience literature on phenomena that lie at the core of social theory and research including moral cognition and behavior and empathy and inter-group attitudes and provides future research questions for interdisciplinary research.